Chronic Inversion of Uterus Following Spontaneous Abortion: A Case Report - Manandhar, Tara; Shah, Deepa; Rijal, Pappu (Journal of BP Koirala Institute of Health Sciences, 2020)
Uterine inversion is a rare entity but poses a serious threat if not diagnosed and managed timely. Here we present a case of chronic uterine inversion in a 30-year-old lady who presented in emergency with a mass coming out per vagina, blood mixed vaginal discharge, and lower pain abdomen for the last 15 days. She underwent laparotomy and was found to have uterine inversion. The patient was attempted for repositioning of uterus with the Huntington’s approach, but it was unsuccessful, hence Haultain’s operation was done with a total abdominal hysterectomy and bilateral salpingectomy with right-sided ovarian cystectomy for a dermoid cyst. Our case emphasizes the importance of keeping chronic uterine inversion as a differential diagnosis in women presenting with pain abdomen, mass, and bleeding per vagina, and with a recent history of second-trimester abortion. Timely recognition, especially in chronic inversion, will decrease the morbidity and mortality associated with this rare but life-threatening condition.